Intragenomic linear amplification of human herpesvirus 6B oriLyt suggests acquisition of oriLyt by transposition. - Stamey, F R (1995)
We identified some passage lineages of human herpesvirus 6 variant B (HHV-6B) strain Z29 that contain as many as 12 tandem copies of a genomic segment that corresponds almost precisely to a previously identified minimal efficient origin of lytic replication (oriLyt). Analysis of nucleotide sequences in the vicinity of the amplified segment suggests that the amplification occurred as a two-step process, with the first step being a rare sequence duplication mediated through directly repeated sequences located near the termini of the amplified segment and the second step occurring via homologous recombination through the duplicated sequence. These results demonstrate that oriLyt has been amplified in some virus stocks and indicate that (i) origin amplification confers a growth advantage on the virus in cell culture and (ii) laboratory-passaged HHV-6B genomes can accommodate additional nucleotide sequences and thus may be useful gene transfer vectors. The structures of the amplified segment and its adjacent sequences together suggest that HHV-6B or a progenitor virus acquired oriLyt by transposition from an unknown source.